Selection of Effective Antibiotics for Uropathogenic Escherichia coli Intracellular Bacteria Reduction - González, María José; Zunino, Pablo; Scavone, Paola; Robino, Luciana (Frontiers in Cellular and Infection Microbiology, 2020)
Urinary tract infections (UTI) are one of the most frequent bacterial infections in humans, being Uropathogenic Escherichia coli (UPEC), the most common etiological agent. The ability of UPEC to invade urothelial cells and to form intracellular bacterial communities (IBC) has been described. Therefore, UPEC can persist in the urinary tract producing recurrent infections, resisting antibiotic activity. The objective of the present work was to analyze the ability of a collection of UPEC clinical isolates to invade bladder epithelial cells in vitro and the activity of different classes of antibiotics on intracellular bacteria. We selected 23 UPEC clinical isolates that had been previously detected intracellularly in desquamated bladder epithelial cells from patients’ urine. A cellular invasion assay using the T24 bladder cell line was used. Intracellular bacteria was confirmed by laser confocal microscopy. All the strains were able to invade the cells with different percentages of intracellular bacterial survival (0.7 to 18%). However, no significant relationship was found between the percentage of in vitro infection and the presence of IBC in desquamated urine cells. In vitro, intracellular bacteria were confirmed in four representative strains by confocal laser microscopy. Ceftriaxone, ciprofloxacin and, azithromycin in vitro activity on intracellular bacteria were evaluated. Amikacin was used as a negative control. All the antibiotics tested, except amikacin, significantly decreased the number of intracellular bacteria. Ciprofloxacin was the antibiotic that induced the highest decrease percentage. Conclusions: All UPEC clinical isolates could invade bladder epithelial cells in vitro. Ceftriaxone, ciprofloxacin, and azithromycin can reduce the percentage of intracellular bacteria in vitro. In vivo studies are needed to confirm the utility of these antibiotics for intracellular bacteria reduction in UTI.